2021
DOI: 10.3390/horticulturae7120574
|View full text |Cite
|
Sign up to set email alerts
|

A Pivotal Role of Chitosan Nanoparticles in Enhancing the Essential Oil Productivity and Antioxidant Capacity in Matricaria chamomilla L.

Abstract: Chitosan is a biopolymer with several biological and agricultural applications. Recently, development of chitosan nanoparticles (CSNPs) adds additional value by further using it as an eco-friendly biostimulant. Therefore, the impact of CSNPs foliar application on the growth, essential oil productivity and antioxidant capacity of chamomile was investigated. Treatments comprised 0, 100, 200, 300 and 400 mg L−1 of CSNPs applied to plants as a foliar spray. CSNPs foliar application improved the growth and producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
2
2
1
Order By: Relevance
“…These comparable results could be attributed to chitosan stimulation of production of plant hormones such as auxins and cytokinins, which promote cell elongation and division, and increase plant growth. Enhanced transportation of nitrogen in functional leaves also supports plant growth and development and enhances plant quality attributes by increasing protein synthesis and chlorophyll production (Mazrou et al, 2021). In contrast to the present results, Kahromi and Khara (2021) found that foliar application of chitosan did not affect biomass of Dracocephalum kotschy.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These comparable results could be attributed to chitosan stimulation of production of plant hormones such as auxins and cytokinins, which promote cell elongation and division, and increase plant growth. Enhanced transportation of nitrogen in functional leaves also supports plant growth and development and enhances plant quality attributes by increasing protein synthesis and chlorophyll production (Mazrou et al, 2021). In contrast to the present results, Kahromi and Khara (2021) found that foliar application of chitosan did not affect biomass of Dracocephalum kotschy.…”
Section: Discussioncontrasting
confidence: 99%
“…Kıtır Sen and Duran (2023) also reported that B. subtilis and B. megaterium led to increased yields of Izmir thyme. Other reports have shown that chitosan can increase essential oil content of thyme (Emami Bistgani et al, 2017), Origanum vulgare (Bharti et al, 2013), and Matricaria chamomilla L. (chamomile) (Mazrou et al, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…Increasing the chlorophyll activity under stressful conditions plays an important role in improving the photosynthesis rate and producing sufficient carbohydrates for cell growth and the production of EO-secreting glands, and in this way, it will be able to increase the EO content in the plant. In accordance with the results of the present study, Mazrou et al [ 36 ] noted that the application of CHT NPs enhanced the EO content of Matricaria chamomilla L. by 57.14% and 47.06% during the two seasons of study. Further, Golubkina et al [ 24 ] showed that the inoculation of AMF with Artemisia dracunculus and Lavandula angustifolia roots enhanced the EO content of both plants by 3% and 18% compared with the untreated control, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…A significant influence of biostimulants on agromorphological characteristics was observed, which is comparable to previous studies on lavandin (Erbas et al, 2017), garden thyme (Thymus vulgaris L.) (Kwiatkowski et al, 2020), and German chamomile (Mazrou et al, 2021). Similar to the present findings, increased plant height and number of branches in Dutch fennel (Foeniculum vulgare Mill.)…”
Section: Discussion Plant Growth and Pigment Investigationsupporting
confidence: 91%